Chlorine-36 Surface Exposure Dating of Late Holocene Moraines and Glacial Mass Balance Modeling, Monte Sierra Nevada, South-Central Chilean Andes (38°S) - Price, Brittany N.; Stansell, Nathan D.; Fernández, Alfonso; Licciardi, Joseph M.; Lesnek, Alia J.; Muñoz, Ariel; Sorensen, Mary K.; Jaque Castillo, Edilia; Shutkin, Tal; Ciocca, Isabella; Galilea, Ianire (Frontiers in Earth Science, 2022)
The development of robust chronologies of Neoglaciation from individual glaciers throughout the high-altitude Andes can provide fundamental knowledge of influences such as regional temperature and precipitation variability, and aid in predicting future changes in the Andean climate system. However, records of Late Holocene glaciation from the Central Chilean Andes are sparse, and often poorly constrained. Here, we present 36Cl surface exposure ages, dendrochronologic constraints, and glacial mass balance modeling simulations of Late Holocene glacier fluctuations in the Central-South Chilean Andes. A series of concentric moraine ridges were identified on Monte Sierra Nevada (38°S), where exposure dating of basaltic boulders was used to establish a chronology of ice recession. We infer that moraine abandonment of the most distal ridge in the valley commenced by ~4.2 ka, and was followed by glacier margin retreat to an up-valley position. Exposure ages of the oldest Late Holocene boulders (~2.5-0.8 ka) along the marginal extents of the moraine complex indicate fluctuations of the glacier terminus prior to ~0.65 ka. A final expansion of the ice margin reoccupied the position of the 4.2 ka moraine, with abatement from the outermost composite moraine occurring by ~0.70 ka, as constrained by tree-ring data from live Araucaria araucana trees. Finally, a series of nested moraines dating to ~0.45-0.30 ka, formed from a pulsed ice recession during the latest Holocene when the lower reaches of the glacial snout was most likely debris mantled. A distributed temperature index model combined with a glacier flow model was used to quantify an envelope of possible climatic conditions of Late Holocene glaciation. The glacial modeling results suggest conditions were ~1.5°C colder and 20% wetter during peak Neoglaciation relative to modern conditions. These records also suggest a near-coeval record of Late Holocene climate variability between the middle and high southern latitudes. Furthermore, this study presents some of the youngest 36Cl exposure ages reported for moraines in the Andes, further supporting this method as a valuable geochronologic tool for assessing Late Holocene landscape development.